Donor pericardium graft repair of traumatic globe rupture at previous trabeculectomy site - Clarke, Jonathan; Shah, Brinda P. (Digital Journal of Ophthalmology, 2014)
A 65-year-old man with a history of bilateral trabeculectomy augmented with mitomycin C underwent surgery for a scleral rupture following trauma. The site of the rupture was a posterior extension of the scleral flap. Attempted closure of a ragged scleral wound was not possible without excessive distortion and induced astigmatism. Persistent hypotony due to over drainage was treated by patching the site with a donor pericardium graft, secured with 10-0 nylon sutures. Although the trabeculectomy became nonfunctional and further glaucoma surgery was eventually required, a good visual outcome was achieved due to early repair following trauma.